Microanatomy of the myocardial extensions of the pulmonary valve in light of modern catheter ablation methodology. (30th June 2021) - Lis, Maciej; Solewski, Bernard; Chrzanowski, Jan; Dudkiewicz, Damian; Strona, Marcin; Jasińska, Katarzyna A.; Wiater, Jerzy; Wartalski, Kamil; Lis, Grzegorz J.; Hołda, Mateusz K.
Abstract: Introduction: The muscular sleeves (or myocardial extensions) derived from the right ventricle infundibulum myocardium are considered the true anatomic substrate for right ventricular outflow tract arrhythmias. Methods: Pulmonary valve specimens obtained from 65 donors (24.6% females, mean age 45.9 ± 15.8 years) were investigated micro‐anatomically. Specimens were histologically processed, stained with Masson's Trichrome, and examined under a light microscope. Results: The myocardial extensions were present in the left anterior pulmonary valve sinus in 86.2% of cases, in the right anterior sinus in 89.2% of cases and in 90.7% of cases in the posterior sinus ( p = .699). In 69.2% of examined hearts, the myocardial extensions were present in all sinuses. The mean height of the extensions was 4.12 ± 1.76 (left anterior) versus 3.69 ± 1.47 (right anterior) versus 4.28 ± 1.73 mm (posterior) ( p = .137). The myocardial extensions occupied an average of 28.9 ± 10.4% of the left anterior sinus, 26.7 ± 11.2% of the right anterior sinus, and 31.9 ± 11.3% of the posterior sinus ( p = .044). Sleeves extending beyond the fibro‐arterial transition zone were present in at least one sinus in 33.8% of hearts (in 7.7% (5/65) of the left and right anterior sinuses and 21.5% (14/65) of posterior sinus, p = .021). Conclusions: The myocardial extensions of the pulmonary valve are common anatomical entities. Although the length of the myocardial sleeves is similar in all pulmonary valve sinuses, their relative extent is greatest in the posterior sinus. Long sleeves that spread beyond the fibro‐arterial transition zone were observed in one‐third of hearts, predominantly in the posterior sinus. Myocardial and fibrous tissue layer thicknesses varied considerably.